The Longitudinal Assessment of Neuropsychiatric Symptoms in Mild Cognitive Impairment and Alzheimer's disease and their Association with White Matter Hyperintensities in the National Alzheimer's Coordinating Center's Uniform Data Set - Anor, Cassandra J. (Biol Psychiatry Cogn Neurosci Neuroimaging, 2020)
INTRODUCTION: Neuropsychiatric symptoms (NPS) are common in Alzheimer’s disease (AD). NPS contribute to patients’ distress, caregiver burden, and institutionalization. White matter hyperintensities (WMH) appear on MRI, usually indicative of cerebrovascular disease. WMH have been associated with certain NPS. We aimed to assess the relationship between WMH and NPS severity in MCI due to AD (MCI-AD) and AD and to assess the ability of WMH to predict NPS progression. Data was obtained from NACC. METHODS: 252 participants (114MCI-AD/138AD) were used in this study. Baseline WMH were quantified using an automated segmentation technique. NPS were measured using the Neuropsychiatric Inventory. Mixed-effect models and correlations were used to determine the relationship between WMH and NPS. RESULTS: Longitudinal mixed-effect models revealed a significant relationship between increase in NPI total scores and baseline WMH (p=0.014). There was a significant relationship between baseline WMH and an increase in delusions (p=0.023), hallucinations (p=0.040), agitation (p=0.093), depression (p=0.017), and irritability (p= 0.002). Correlation plot analysis showed that baseline whole brain WMH predicted change in future NPI total scores (r=0.169, p=0.008) and predicted change in future agitation severity scores (r= 0.165, p= 0.009). WMH in the temporal (r=0.169, p=0.008) and frontal (r=0.153, p=0.016) lobes contributed most to this change. CONCLUSION: Depression, irritability, and agitation are common NPS and very distressful to patients and caregivers. Our findings of increased NPS severity over time in MCI-AD and AD with increased WMH have important implications for treatment, arguing for aggressive treatment of vascular risk factors in patients with MCI-AD and AD.